THE EFFECT OF EXECUTIVE COMPENSATION, REPRESENTATION OF CHIEF FINANCIAL OFFICER'S WOMEN, EXECUTIVE CHARACTERISTIC ON TAX AGGRESSIVENESS - Sugiyarti, Listya (Universitas Negeri Yogyakarta, 2021)
Abstract: The Effect of Executive Compensation, Representation of Chief Financial Officer's Women, Executive Characteristic on Tax Aggressiveness. The purpose of this study was to determine the effect of executive compensation, female CFO representation, executive characteristics on tax aggressiveness in companies listed on the Indonesia Stock Exchange for the period 2013-2017. The population in this study were manufacturing companies on the Indonesia Stock Exchange for the period 2013-2017. The number of manufacturing companies sampled in this study were 12 companies with 5 years of observation. Based on the purposive sampling method, the total sample is 60 financial report data. This study uses multiple linear regression analysis techniques, t test with the application of the SPSS 24 program. The results of this research showed that the variables of executive compensation have a positive and significant impact on aggressiveness tax, Representation of Chief Financial Officer (CFO) Women has no significant on aggressiveness tax, and the variable executive characteristic has a negative and significant impact on aggressiveness tax. Simultaneously, executive compensation, Representation of Chief Financial Officer (CFO) Women and executive characteristics have an impact on tax aggressiveness.Keywords: Executive Compensation, Representation of Chief Financial Officer (CFO) Women, Executive Characteristics, Tax Aggressiveness Abstrak: Pengaruh Kompensasi Eksekutif, Keterwakilan CFO Wanita, Karakteristik Eksekutif terhadap Agresivitas Pajak. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh kompensasi eksekutif, keterwakilan CFO wanita, karakteristik eksekutif terhadap agresivitas pajak pada perusahaan yang terdaftar di Bursa Efek Indonesia periode 2013-2017. Populasi dalam penelitian ini adalah perusahaan manufaktur di Bursa Efek Indonesia periode 2013-2017. Jumlah perusahaan manufaktur yang dijadikan sampel dalam penelitian ini adalah 12 perusahaan dengan pengamatan selama 5 tahun. Berdasarkan metode purposive sampling, total sampel adalah 60 data laporan keuangan. Penelitian ini menggunakan tehnik analisis regresi linier berganda, uji t dengan aplikasi program SPSS 24. Hasil penelitian ini menunjukkan bahwa secara parsial variabel kompensasi eksekutif berpengaruh positif dan signifikan terhadap agresivitas pajak, keterwakilan CFO wanita tidak berpengaruh signifikan terhadap agresivitas pajak, dan karakteristik eksekutif memiliki pengaruh negatif dan signifikan terhadap pajak agresivitas.Kata kunci: Kompensasi Eksekutif, Keterwakilan CFO Wanita, Karakteristik Eksekutif, Agresivitas Pajak